2019
DOI: 10.3390/rs11171977
|View full text |Cite
|
Sign up to set email alerts
|

Radar Measurements of Morphological Parameters and Species Identification Analysis of Migratory Insects

Abstract: Migratory insect identification has been concerning entomology and pest managers for a long time. Their nocturnal behavior, as well as very small radar cross-section (RCS), makes individual detection challenging for any radar network. Typical entomological radars work at the X-band (9.4 GHz) with a vertical pencil beam. The measured RCS can be used to estimate insect mass and wingbeat frequency, and then migratory insects can be categorized into broad taxon classes using the estimated parameters. However, curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Individual mass is the most important single feature differentiating insect radar signals [ 69 ], which has been used for echo selection [ 63 ] and to infer species identity in combination with aerial trapping [ 70 ]. Parameters related to body shape have been used to select echoes from morphologically distinct taxa such as ladybird beetles and hoverflies, particularly in systems where the composition of aerial taxa has been well-described.…”
Section: Current State Of Radar-based Biodiversity Monitoring Of Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual mass is the most important single feature differentiating insect radar signals [ 69 ], which has been used for echo selection [ 63 ] and to infer species identity in combination with aerial trapping [ 70 ]. Parameters related to body shape have been used to select echoes from morphologically distinct taxa such as ladybird beetles and hoverflies, particularly in systems where the composition of aerial taxa has been well-described.…”
Section: Current State Of Radar-based Biodiversity Monitoring Of Insectsmentioning
confidence: 99%
“…Machine learning approaches to differentiate insects based on a limited set of morphological parameters are rapidly improving and, e.g. allowed identifying 23 Lepidoptera and Odonata species in an aerial community in East China with a probability greater than 0.5 [ 69 ]. The importance of various characteristics in differentiating taxa depends on type and range of taxa being classified.…”
Section: Current State Of Radar-based Biodiversity Monitoring Of Insectsmentioning
confidence: 99%
“…A key problem of multitarget tracking in cluttered environments is the uncertainty of measurement-to-track data associations, which means it is difficult to correctly determine the sources of measurements by only relying on kinematic information (target position and velocity). According to the previous literature [24,25], it can be concluded that an insect's polarization pattern and scattering matrix (SM) are closely related to the insect's geometry and composition, which can be measured using a fully polarimetric radar. This type of radar can measure all four linear-polarization receive-transmit (HH, HV, VH, VV) backscattering combinations.…”
Section: Multidimensional Feature Fusion Strategymentioning
confidence: 99%